Elastography Validity Criteria Definition Using Numerical Simulations and MR Acquisitions on a Low-Cost Structured Phantom - Yushchenko, Maksym; Sarracanie, Mathieu; Amann, Michael; Sinkus, Ralph; Wuerfel, Jens; Salameh, Najat (Frontiers in Physics, 2021)
MR Elastography is a novel technique enabling the quantification of mechanical properties in tissue with MRI. It relies on a three-step process that includes the generation of a mechanical vibration, motion capture using dedicated MR sequences, and data processing involving inversion algorithms. If not properly tuned to the targeted application, each of those steps may impact the final outcome, potentially causing diagnostic errors and thus eventually treatment mismanagement. Different approaches exist that account for acquisition or reconstruction errors, but simple tools and metrics for quality control shared by both developers and end-users are still missing. In this context, our goal is to provide an easily deployable workflow that uses generic validity criteria to assess the performance of a given MRE protocol, leveraging numerical simulations with an accessible experimental setup. Numerical simulations are used to help both determining sets of relevant acquisition parameters and assessing the data processing’s robustness. Simple validity criteria were defined, and the overall pipeline was tested in a custom-built, structured phantom made of silicone-based materials. The latter have the advantage of being inexpensive, easy to handle, facilitate the fabrication of complex structures which geometry resembles the anatomical structures of interest, and are longitudinally stable. In this work, we successfully tested and evaluated the overall performances of our entire MR Elastography pipeline using easy-to-implement and accessible tools that could ultimately translate in MRE standardized and cost-effective procedures.